The miraculous baby - Khan, Saniyasnain (GOODWORD BOOKS S.l., 2022)
"The Miraculous Baby: Quran Stories for Little Hearts" is a beautifully illustrated children's book that narrates the story of the miraculous birth of Prophet Isa (Jesus) from his mother, Maryam (Mary). The tale emphasizes themes of faith, hope, and divine intervention as it recounts how Maryam faced challenges and skepticism during her pregnancy, yet remained steadfast in her belief in Allah's plan. Designed to introduce young readers to important Islamic teachings, the book presents the story in an engaging and age-appropriate manner, encouraging children to learn about the significance of faith and the power of miracles in their lives.